Pemanfaatan Teknologi Irigasi Otomatis dan Sensor Kelembaban Tanah dalam Mendukung Efisiensi Air dan Ketahanan Pangan Berkelanjutan - Parwito; Eko Sumartono (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Limited water resources and increasing global food demand require the application of efficient and sustainable agricultural technologies. This study examines the use of soil moisture sensor-based automatic irrigation technology to improve water efficiency and support sustainable food security through literature review and secondary data analysis. The results show that this technology can save water usage by 30–50%, increase crop productivity by up to 25%, and reduce long-term operational costs. The system works by continuously monitoring soil moisture and regulating water supply according to crop needs. The main challenges include initial investment costs, farmers' limited knowledge, and supporting infrastructure, but these can be overcome through policy support, training, and appropriate business models. This study recommends the development of affordable automated irrigation systems, increased farmer capacity, and comprehensive policies to accelerate the adoption of this technology at the field level.